Techno-economic analysis for the production of LaNi5 particles - Nandiyanto, Asep Bayu Dani; Maulana, Muhammad Irfansyah; Raharjo, Jarot; Sunarya, Yayan; Minghat, Asnul Dahar (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2020)
LaNi5 is widely used in various applications. Many methods to produce LaNi5 particles have been reported but information for the large-scale production, so far, is less available. This study aimed to evaluate the project for the production of LaNi5 particles using combustion-reduction (CR) and co-precipitation-reduction (CPR) methods based on engineering and economic perspective. Engineering evaluation was conducted by evaluating the CR and CPR processes from stoichiometry. For the economic evaluation, several economic parameters were calculated in the ideal condition including gross profit margin (GPM), payback period (PBP), break-even point (BEP), cumulative net present value (CNPV), profitability index (PI), internal rate return (IRR), and return on investment (ROI). For the worst cases in the project, it was done by calculating both the internal problems (i.e., raw materials, sales, utility, labor, employee, fixed cost, variable cost, and production capacity) and the external issues (i.e., taxes and subsidiaries). The engineering analysis provided the information that CR and CPR projects are prospective for being able to be done using commercial apparatuses. The economic analysis from GPM, PBP, BEP, CNPV, and PI showed the positive results, while IRR and ROI showed the negative ones, indicating that the projects are acceptable for large-scale production, but it seems to be less attractive for industrial investors. The analysis also confirmed that the CR process was more prospective than the CPR process. This work has demonstrated the important of the projects for further developments.